(untitled) (Research, Society and Development, 2021)
Phyla betulifolia (Kunth) Greene is commonly known as sweet grass and deserves to be highlighted for its medicinal potential. According to traditional communities in the Amazon region, it helps in controlling diabetes, in addition to having a calming action. One of the initial steps for the knowledge of the different species is the study of their biology and in particular of their phenology, since it refers to the part of botany that studies the different stages of growth and development of plants, both vegetative and reproductive, demarcating them the times of occurrence and the respective characteristics. This work aimed to evaluate the reproductive phenological frequency of Capim doce, relating to the climatic conditions of average air temperature and rainfall, aiming to specify the most appropriate time to collect the plant material for medicinal use and propagation of the species. Considering 10 individuals of Capim Doce, the frequency evaluation of the phenophases was carried out in the morning for five days a week, recording the occurrence of the phenophases, from 2014 to 2019. The Capim Doce presented the reproductive phase during the entire evaluated period, occurs under the influence of climatic elements in the flowering of the species. Fruiting was not influenced by rainfall and average air temperature. The collection of plant material of this species for medicinal use must be carried out in the period of the least number of days of the phenophases and for the propagation it can be collected throughout the year.